Developing narrative comprehension multilingual assessment instrument for narratives - Bohnacker, Ute; Gagarina, Natalia (Studies in Bilingualism,, 2020)
"Comprehension of texts and understanding of questions is a cornerstone of successful human communication. Whilst reading comprehension has been thoroughly investigated in the last decade, there is surprisingly little research on children's comprehension of picture stories, particularly for bilinguals. This can be partially explained by the lack of cross-culturally robust, cross-linguistic instruments targeting early narration. This book presents an inference-based model of narrative comprehension and a tool that grew out of a large-scale European project on multilingualism. Covering a range of language settings, the book uses the Multilingual Assessment Instrument for Narratives to answer the question which narrative comprehension skills (bilingual) children can be expected to master at a certain age, and explores how such comprehension is affected (or not affected) by linguistic and extra-linguistic factors. Linking theory to method, the book will appeal to researchers in linguistics and psychology and graduate students interested in narrative, multilingualism, and language acquisition"--